ATTENUATED TOTAL REFLECTION-FOURIER-TRANSFORM INFRARED AND 27AL-NUCLEAR MAGNETIC RESONANCE INVESTIGATION OF SPECIATION AND COMPLEXATION IN AQUEOUS AL(III)-PICOLINATE SOLUTIONS - Loring J.S.; Karlsson M.; Fawcett W.R.; Casey W.H. (My University, 2000)
The speciation and infrared spectra of aqueous solutions containing dissolved aluminum and picolinic acid (2-pyridinecarboxylic acid) were investigated using a combination of attenuated total reflection Fourier-transform infrared and 27Al-nuclear magnetic resonance spectroscopies. Conditional equilibrium constants at an apparent ionic strength of 1.5 M are reported for the protonation of picolinate and the formation of Al(III)-picolinate complexes. The resolved infrared spectra of picolinic acid and the picolinate ion are assigned and evidence is presented that picolinic acid exists predominantly as a zwitterion in solution. It is demonstrated that the infrared spectra of the AlL2+ and AlL2+ complexes are indistinguishable within the limits of our uncertainty. The assignment of the spectrum of the Al(III)-picolinate complexes indicates that picolinate is coordinated bidentate to Al(III) through both the nitrogen of the pyridine ring and one of the oxygens of the carboxylate substituent. We hypothesize that an inner-sphere surface complex on an Al(III)-(hydr)oxide surface, if formed, will involve bidentate coordination of picolinate to aluminum and have an infrared signature similar to that determined here for the solution-phase Al(III)-picolinate complexes.